A20 controls RANK‐dependent osteoclast formation and bone physiology. (4th October 2022) - Martens, Arne; Hertens, Pieter; Priem, Dario; Rinotas, Vagelis; Meletakos, Theodore; Gennadi, Meropi; Van Hove, Lisette; Louagie, Els; Coudenys, Julie; De Muynck, Amélie; Gaublomme, Djoere; Sze, Mozes; et al.
Abstract: The anti‐inflammatory protein A20 serves as a critical brake on NF–κB signaling and NF–κB‐dependent inflammation. In humans, polymorphisms in or near the TNFAIP3/A20 gene have been associated with several inflammatory disorders, including rheumatoid arthritis (RA), and experimental studies in mice have demonstrated that myeloid‐specific A20 deficiency causes the development of a severe polyarthritis resembling human RA. Myeloid A20 deficiency also promotes osteoclastogenesis in mice, suggesting a role for A20 in the regulation of osteoclast differentiation and bone formation. We show here that osteoclast‐specific A20 knockout mice develop severe osteoporosis, but not inflammatory arthritis. In vitro, osteoclast precursor cells from A20 deficient mice are hyper‐responsive to RANKL‐induced osteoclastogenesis. Mechanistically, we show that A20 is recruited to the RANK receptor complex within minutes of ligand binding, where it restrains NF–κB activation independently of its deubiquitinating activity but through its zinc finger (ZnF) 4 and 7 ubiquitin‐binding functions. Together, these data demonstrate that A20 acts as a regulator of RANK‐induced NF–κB signaling to control osteoclast differentiation, assuring proper bone development and turnover. Synopsis: The anti‐inflammatory protein A20 acts as a critical inhibitor of NF‐κB signaling and NF‐κB‐dependent inflammation. This study uncovers a new role for A20 in the regulation of RANK‐induced NF‐κB signaling, osteoclastogenesis, and bone physiology. Osteoclast‐specific A20 knockout mice develop severe osteoporosis, but not inflammatory arthritis. Osteoclast precursor cells from A20 deficient mice are hyper‐responsive to RANKL‐induced osteoclastogenesis. A20 is recruited to the RANK receptor complex upon ligand binding. A20 restrains NF‐κB activation through its zinc finger and ubiquitin‐binding function. Abstract : The anti‐inflammatory protein A20 acts as a critical inhibitor of NF‐κB signaling and NF‐κB‐dependent inflammation. This study uncovers a new role for A20 in the regulation of RANK‐induced NF‐κB signaling, osteoclastogenesis, and bone physiology.